2016
DOI: 10.1186/s12860-016-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical imaging: a new concept for targeted imaging of large volumes from cells to tissues

Abstract: BackgroundImaging large volumes such as entire cells or small model organisms at nanoscale resolution seemed an unrealistic, rather tedious task so far. Now, technical advances have lead to several electron microscopy (EM) large volume imaging techniques. One is array tomography, where ribbons of ultrathin serial sections are deposited on solid substrates like silicon wafers or glass coverslips.ResultsTo ensure reliable retrieval of multiple ribbons from the boat of a diamond knife we introduce a substrate hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…In the published AT procedure, the array of sections is moved to the rear edge of the coverslip where it touches the interface between the glass and the water (Micheva and Smith, 2007). To attach the sections to support, water is drained from the side of the knife boat using a syringe (Micheva and Smith, 2007), or the coverslip is pulled out of the trough using a micromanipulator (Horstmann et al, 2012;Wacker et al, 2016). In our hands, this method compromises the control of water during draining.…”
Section: Modified Diamond Knifementioning
confidence: 99%
“…In the published AT procedure, the array of sections is moved to the rear edge of the coverslip where it touches the interface between the glass and the water (Micheva and Smith, 2007). To attach the sections to support, water is drained from the side of the knife boat using a syringe (Micheva and Smith, 2007), or the coverslip is pulled out of the trough using a micromanipulator (Horstmann et al, 2012;Wacker et al, 2016). In our hands, this method compromises the control of water during draining.…”
Section: Modified Diamond Knifementioning
confidence: 99%
“…These attributes establish AT as an ideal choice for the most demanding analyses of diverse cellular architectures within mature and developing tissues, including brain. This essay will draw examples mainly from neuroscience, but AT methods are also finding many cell and tissue biology applications outside of neuroscience [ 1 13 ].…”
Section: What Is Array Tomography?mentioning
confidence: 99%
“…Various implementations and applications of AT are described in detail by excellent recent reviews [ 1 3 , 6 , 14 16 ]. Features common to all AT implementations include: (A) physical ultrathin serial sectioning of a fixed, resin-embedded specimen, (B) collection of the resulting serial sections to form an array on a solid substrate, (C) staining and digital imaging of the resulting serial section array by fluorescence microscopy (FM-AT) and/or electron microscopy (EM-AT), and (D) computational stitching of the resulting two-dimensional image tiles into coherent volumetric images.…”
Section: What Is Array Tomography?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the machine used in the ATUM method is expensive. Horstmann et al [ 4 ] and Wacker et al [ 10 ] have also reported a device for silicon substrate positioning. In their approach, the silicon substrate is clipped using forceps attached to a custom-built manipulator and a long ribbon is pulled out in a longitudinal direction from the water.…”
mentioning
confidence: 99%